Serum irisin concentration and its association with muscle and fat mass in aerobic and anaerobic endurance athlete men and women - Ahmad, M. N.; Abu Al Haija, D. M. (Trends in Sport Sciences, 2023)
Introduction. Irisin is released in response to exercise, but the regulatory effect of exercise on serum irisin is controversial. Evidence linking irisin with muscle mass or fat mass is limited. Little is known about the connection of irisin with the type and intensity of exercise in athletes. Aim of Study. This study sought to determine serum irisin concentration (SIC) in athletes and non-athletes and assess its association with anthropometric indices, including body weight (BW), body mass index (BMI), waist-to-height ratio (WHtR), mid-upper arm circumference (MUAC), lean body mass (LBM), and fat mass (FM). Material and Methods. We conducted a case-control study on 72 athletes and non-athletes comprising three age-and sex- -matched groups with a 1 : 1 sex ratio: 24 footballers (aerobic endurance exercise), 24 bodybuilders (anaerobic strength exercise), and 24 non-exercised controls. Standard protocols for measuring anthropometric indices and quantifying SIC were followed. Results. Whole athletes had higher SIC than controls, with footballer men and women having higher values than bodybuilders and controls. Athletic men and women exhibited higher SIC than control men. SIC showed no sex differences within each experimental and control group. SIC negatively correlated with BW, BMI, LBM, MUAC, and WHtR in athlete women, BMI and MUAC in bodybuilders, FM in whole footballers, and BW in total control, but positively correlated with overall bodybuilders. Conclusions. The findings indicate that irisin is exercise-dependent, as it is enhanced in aerobic endurance more than in anaerobic strength exercise but is gender-independent. The results also support the relationship between irisin and body composition, as it generally correlates negatively with BW, BMI, FM, and WHtR.